Dried spot sample and its drug detection using LC-MS/MS: Trends and advances in matrix collection and bioanalytics - Arpita Sathyanarayanan, Divyashree Mysore Somashekara (Journal of Applied Pharmaceutical Science, 2022)
Therapeutic drug monitoring involves the clinical study of the drug and its metabolite in a biological matrix amidst the existing endogenous substances. One of the key components in performing therapeutic drug monitoring is the biological matrix. The collection and storage of biological matrix have developed rapidly in the last few decades. Dried blood spot (DBS) is a method which was introduced in the 1960s and has gone through series of advanced till date. These involve use of filter paper or punch cards to harvest and store blood for further use. One of the major disadvantages of DBS is the influence of hematocrit values in drug collections therefore paving way for dried plasma spot detection (DPS). Use of DBS and DPS is a growing trend observed in the sample collection. In the last few years, many assays have been developed based on this technique this paper introduced the pross and cons of DBS and DPS while looking into the advances in the drug detection using these matrixes.
Keywords: Drug monitoring, dried blood spots, dried plasma spots, protein precipitation, bioanalysis, haematocrit.